PROSEDUR SISTEM INFORMASI AKUNTANSI PENERIMAAN KAS SEBAGAI PENGENDALIAN INTERN PADA UNIT TOSERBA KOPERASI KELUARGA BESAR PT SEMEN PADANG - Jurnal Ilmiah Manajemen UPB (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2017)
The purpose of this study is to look at the accounting information system of cash receipts in the unit of Family Cooperative of PT Semen Padang. This research uses descriptive approach. Hail research explains that 1)The department store unit is one of the units that provides daily needs, where all cash receipts come from sales in cash or credit. Cash sales at department stores are open to the public and members whereas, credit sales are for members of the cooperative who are directly employees, 2) cash sales are over the-counter sale, buyers (costumer) come directly to the department store to make daily purchases By issuing cash payments to the cashier on goods purchased, 3) The credit sales from the department store unit in the form of a system of receivable penning is done by deducting the salary of the employee through the treasurer of each member company so that the credit payment never stalled. The author suggests the implementation of transaction entries that have been using computerization, should also make the process of data processing using information technology in the form of application programs in cash management in the company.